2020
DOI: 10.1021/acsanm.9b02223
|View full text |Cite
|
Sign up to set email alerts
|

Partially Oxidized Ti3C2Tx MXenes for Fast and Selective Detection of Organic Vapors at Part-per-Million Concentrations

Abstract: MXenes, two-dimensional transition metal carbides or nitrides, have recently shown great promise for gas sensing applications. We demonstrate that the sensitivity of intrinsically metallic Ti3C2T x MXene can be considerably improved via its partial oxidation in air at 350 °C. The annealed films of MXene sheets remain electrically conductive, while their decoration with semiconducting TiO2 considerably improves their chemiresistive response to organic analytes at low-ppm concentrations in dry air, which was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 45 publications
4
69
0
Order By: Relevance
“…In its pristine form, the flake thickness is about 2.4 nm, which is similar to the values reported in our previous works for monolayer Ti 3 C 2 T x measured on a Si/SiO 2 substrate. 6,35 Interestingly, we previously observed a smaller AFM height of about 1.6 nm for the monolayer Ti 3 C 2 T x flakes lying on top of other flakes. 7,35 We suggested that the flakes lying directly on Si/SiO 2 appear thicker in AFM measurements than the flakes lying on other flakes because apparently there is a larger number of adsorbed molecules, such as water, at the Ti 3 C 2 T x /SiO 2 interface than between the Ti 3 C 2 T x layers.…”
Section: Electronic Properties Of Ti 3 C 2 T X Devicesmentioning
confidence: 87%
See 1 more Smart Citation
“…In its pristine form, the flake thickness is about 2.4 nm, which is similar to the values reported in our previous works for monolayer Ti 3 C 2 T x measured on a Si/SiO 2 substrate. 6,35 Interestingly, we previously observed a smaller AFM height of about 1.6 nm for the monolayer Ti 3 C 2 T x flakes lying on top of other flakes. 7,35 We suggested that the flakes lying directly on Si/SiO 2 appear thicker in AFM measurements than the flakes lying on other flakes because apparently there is a larger number of adsorbed molecules, such as water, at the Ti 3 C 2 T x /SiO 2 interface than between the Ti 3 C 2 T x layers.…”
Section: Electronic Properties Of Ti 3 C 2 T X Devicesmentioning
confidence: 87%
“…6,35 Interestingly, we previously observed a smaller AFM height of about 1.6 nm for the monolayer Ti 3 C 2 T x flakes lying on top of other flakes. 7,35 We suggested that the flakes lying directly on Si/SiO 2 appear thicker in AFM measurements than the flakes lying on other flakes because apparently there is a larger number of adsorbed molecules, such as water, at the Ti 3 C 2 T x /SiO 2 interface than between the Ti 3 C 2 T x layers. 7 Figure 4C shows that, after the current breakdown, the majority of the flake has the thickness reduced by about 0.8 nm down to 1.6 nm.…”
Section: Electronic Properties Of Ti 3 C 2 T X Devicesmentioning
confidence: 87%
“…[16] So far, Ti 3 C 2 T x has proved being sensitive to rather low concentrations of ketones (< to 50 ppb), alcohols (< to 100 ppb), and ammonia (< to 100 ppb) vapors at room temperature maturing from the impact of the analyte's physical adsorption changing the electronic properties in these low-noise materials. [17][18][19][20][21][22] To further improve sensing properties of Ti 3 C 2 T x MXenes with respect to organic vapors, various approaches have been proposed including partial oxidizing at elevated temperatures up to 350 °C [23] and composing hybrid hetero-composites. [24] While most studies focus on Ti 3 C 2 T x , investigations are not limited to Ti-based MXenes; other M-elements are currently successfully employed with extensive functional characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Energy band diagram of the interface between pristine and oxidized MXene regions based on the UPS data; WF is a work function, F is a Fermi level, E c and E v are conduction and valence bands, respectively. Adapted with permission [136]. Copyright 2018, American Chemical Society.…”
mentioning
confidence: 99%